Optimizing Code-Based Cryptography for Efficient and Secure Post-Quantum Key Agreement - Iqbal, Syed Shamikh; Zafar, Aasim (Procedia computer science, 2025)
Due to the quantum computing threat, RSA and ECC cryptography are at risk, necessitating the need for post-quantum cryptography. Code-based cryptographic schemes, such as the McEliece system, have shown promise due to their resistance to quantum attacks. However, these schemes suffer from large key sizes and high computational complexity, making them unsuitable for resource-constrained devices like IoT. This paper proposes a lightweight key agreement protocol utilizing code-based cryptography optimized for such environments. The protocol reduces key size by 80% (from 1000 KB to 200 KB), computational overhead by 66% (from 15 ms to 5 ms), and energy consumption by 60% (from 2.5 mJ to 1.0 mJ), compared to traditional McEliece-based systems. The inclusion of the Fujisaki-Okamoto transform ensures CCA2 security. Security analysis confirms robustness against classical and quantum adversaries, including Shor’s and Grover’s algorithms. These improvements make the protocol highly suitable for lightweight applications, paving the way for secure post-quantum communication in constrained environments. Future work will address real-world scalability and side-channel attack resistance.